(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
The objective of this study was to formulate an oral sustained release delivery system of sodium diclofenac(DS) based on sodium alginate (SA) as a hydrophilic carrier in combination with chitosan (CH) and sodium carboxymethyl cellulose (SCMC) as drug release modifiers to overcome the drug-related adverse effects and to improve bioavailability. Microspheres of DS were prepared using an easy method of ionotropic gelation. The prepared beads were evaluated for mean particle size, entrapment efficiency, swelling capacity, erosion and in-vitro drug release. They were also subjected to various studies such as Fourier Transform Infra-Red Spectroscopy (FTIR) for drug polymer compatibility, Scanning Electron Microscopy for surface morphology, X-ray Powder Diffraction Analysis (XRD) and Differential Scanning Calorimetric Analysis (DSC) to determine the physical state of the drug in the beads. The addition of SCMC during the preparation of polymeric beads resulted in lower drug loading and prolonged release of the DS. The release profile of batches F5 and F6 showed a maximum drug release of 96.97 ± 0.356% after 8 h, in which drug polymer ratio was decreased. The microspheres of sodium diclofenac with the polymers were formulated successfully. Analysis of the release profiles showed that the data corresponds to the diffusion-controlled mechanism as suggested by Higuchi.